saca paréntesis y resuelve a) (-8)+(+3)= b) (-8)+(-3)= c) (-8)-(+3)=-8-3=(-11) d) (-8)-(-3)= e) (+7)+(+3)= f)

saca paréntesis y resuelve
a) (-8)+(+3)=
b) (-8)+(-3)=
c) (-8)-(+3)=-8-3=(-11)
d) (-8)-(-3)=
e) (+7)+(+3)=
f) (+5)+(-2)=
g) (+2)+(-8)=
h) (-8)+(+15)=
i) 24-(-12)=
j) (-12)+(+4)=
k) (-7-(+4)=
l) (-5)-(+5)=
m) (-6)-(-10)=
n) (-3)-(-11)=
o) (-9)-(-13)=
p) 49-(-1)=
q) -73-(-60)=
r) 36+(-6)=​

1 comentario en «saca paréntesis y resuelve a) (-8)+(+3)= b) (-8)+(-3)= c) (-8)-(+3)=-8-3=(-11) d) (-8)-(-3)= e) (+7)+(+3)= f)»

  1. Explicación paso a paso:

    a) (-8)+(+3)=-8+3=-5

    b) (-8)+(-3)=-8-3= -11

    c) (-8)-(+3)=-8-3=(-11)

    d) (-8)-(-3)= – 8+3= – 5

    e) (+7)+(+3)=7+3= 10

    f) (+5)+(-2)=5 – 2= 3

    g) (+2)+(-8)= 2-8= – 6

    h) (-8)+(+15)= – 8+15= 7

    i) 24-(-12)= 24+12= 36

    j) (-12)+(+4)= – 12+4= – 8

    k) (-7-(+4)= – 7-4= – 11

    l) (-5)-(+5)= – 5-5= – 10

    m) (-6)-(-10)= – 6+10= 4

    n) (-3)-(-11)= – 3+11= 8

    o) (-9)-(-13)= – 9+13= 4

    p) 49-(-1)= 49+1=50

    q) -73-(-60)= – 73+60= – 13

    r) 36+(-6)=36 – 6=30

Deja un comentario